The impact of concurrent linguistic tasks on participants' identification of spearcons. (November 2019) - Davidson, Thomas; Ryu, Youn Ji; Brecknell, Birgit; Loeb, Robert; Sanderson, Penelope
Abstract: Spearcons (time-compressed speech) may be a viable auditory display for patient monitoring; however, the impact of concurrent linguistic tasks remains unexamined. We tested whether different concurrent linguistic tasks worsen participants' identification of spearcons. Experiment 1 tested non-clinician participants' identification of multiple-patient spearcons representing 2 vital signs of 5 patients while participants performed no concurrent task, reading, or saying linguistic tasks. Experiment 2 tested non-clinician participants' identification of 48 single-patient spearcons while they performed no concurrent task, reading, listening, and saying linguistic tasks. In Experiment 1 the saying task worsened participants' identification of spearcons compared with no concurrent task or reading. In Experiment 2, the saying and listening tasks reduced participants' accuracy at identifying spearcons, but the reading task did not. Listening affected identification accuracy no differently than the saying task did. Concurrent auditory linguistic tasks worsen participants' identification of spearcons, probably due to auditory modality interference in verbal working memory. Highlights: Spearcons (time-compressed speech) may be viable for patient monitoring. However, concurrent linguistic tasks may compromise spearcon identification. Results showed spearcon identification worsened with listening and s aying tasks. Spearcon identification did not worsen with a reading task. Auditory linguistic tasks may interfere with spearcons in verbal working memory.